G415(P) A Re-audit of Vitamin supplementation levels in paediatric allergy and general paediatric populations – Any better now than in 2009?. (7th April 2014) - Lwin, T; Coren, M; Joshi, A; Gore, C
Abstract : Introduction: Vitamin D deficiency and rickets are increasing in the United Kingdom, despite national guidance to supplement all children <5 years of age. We previously (2009) surveyed children attending our general paediatric as well as paediatric allergy clinics and found very low supplementation rates in the general paediatric clinic population (13.6%) compared to those in allergy clinics (33%). The findings led to focussed training in the department. Aims: To assess whether increased training and awareness of vitamin supplementation in the context of general paediatrics and paediatric allergy have improved uptake. Method: All children (age 0–16 years)/their parents or carers attending general paediatric clinic (GPC) or paediatric allergy outpatient clinic (PAC) were invited to participate in a self-administered prospective, cross-sectional questionnaire survey throughout the month of June 2013 (previous survey July/August 2009). Results: In 2013, 102 GPC (Mean age= 6.7years, SD 4.91) and 109 PAC (Mean age=6.4, SD=4.01) children were surveyed; 2009: n = 100 GPC; n = 200 PAC. Supplementation rates improved significantly GPC 2009 13.6% vs. 2013 55% supplemented; PAC 2009 33% vs. 2013 49% supplemented. Ethnic origin was not significantly different between the GPC vs. PAC groups in either 2013 or 2009 (GPC 2009/2013: White 35/41%, Afro-Caribbean 28/20%, Asian/Middle Eastern 20/13%, mixed race 6/9%, other 11/17%). Unlike 2009 (white and afro-caribbean children significantly less likely to receive supplements, p = 0.047), there was no difference in likelihood to supplement between ethnic groups in 2013. In both groups, parents largely decided themselves to start supplements (GPC 40% self, ; PAC 49% self, 8.1% dietetian's advice). In the PAC group, having seen a dietitian was not related to increased supplementation rates. Children with multiple food allergies were significantly more likely to receive supplements (>=4 food allergies, 70.8% supplemented vs. no food allergies, 26.1% supplemented; p < 0.01) Conclusion: Compared with the previous audit, vitamin D uptake has improved in the paediatric population, but appears static at <=55% despite high staff awareness and even amongst those who had dietetic advice. Although improved healthcare professional training and advice have increased Vitamin D supplementation rates, there may be other, parental/family/financial/cultural factors inhibiting uptake, which need further exploration.